IMPLEMENTASI METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) PADA SISTEM PENDUKUNG KEPUTUSAN SANKSI PELANGGARAN TATA TERTIB SEKOLAH (STUDI KASUS MA DARUL HIKMAH) - Susilowati , Fisa; Mashuri , Chamdan (Inovate, 2024)
Darul Hikmah Islamic Senior High School have rules and codes of ethics that students must obey, but often these rules and codes of ethics are violated. Every violator will be given punishment and action by the Counseling Guidance teacher. Punishments given can also trigger new problems if considered subjective, objectivity factors between teachers can be different, causing disagreements when giving sanctions and assessments to students. SMART is a method used to assess various different attributes in a decision support system. This method is used to determine penalties for violating the school's code of ethics by assessing various attributes such as the type of violation, the level of error, the number of violations committed. Each attribute is scored based on predetermined criteria. The total score of each alternative will determine the sanctions that will be given to the violators. The results of the research on the Decision Support System for Punishment of School Rules Violations using the (SMART) Method, namely the Guidance and Counseling Teachers can log in and enter the admin dashboard page, can process student data, can input student data violation data, sanctions data, action data, summons, and change password. From testing the process of calculating student rule violations with the SMART method, it can be used and implemented into a decision support system to determine what punishment and actions are obtained by students who violate student rules at MA Darul Hikmah Bandungsari automatically. Keywords: Decision Support System, Regulations, Violation Punishment, SMART